2021
DOI: 10.3390/ijerph18126491
|View full text |Cite
|
Sign up to set email alerts
|

Training and Profile of Special Olympics Portugal Coaches: Influence of Formal and Non-Formal Learning

Abstract: Since coaches play an important role in the development of athletes, the process and mechanisms used by Special Olympics Portugal to develop coaches’ skills are worthy of research. In this context, the study aims to identify the training paths and profiles of the Special Olympics Portugal coach. It also aims to analyze the relationship between formal and non-formal learning in the profile and training of this type of coach. The research is descriptive and transversal regarding Special Olympics Portugal coaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…In another study, coach profiles measured using the Coaches’ Orientation Questionnaire 60 revealed that coaches’ practices were mainly classified as critical, followed by innovative and dialoguing. 48…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, coach profiles measured using the Coaches’ Orientation Questionnaire 60 revealed that coaches’ practices were mainly classified as critical, followed by innovative and dialoguing. 48…”
Section: Resultsmentioning
confidence: 99%
“…A recent quantitative study completed by Pires et al 48 with 50 Portuguese Special Olympics coaches also examined coaches' knowledge sources. Their sources of knowledge were measured using the Coaches' Training Profile Questionnaire.…”
Section: Coach Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the outcomes of a recently published quantitative survey (Healy, 2022) indicated that individuals who report having a disability were significantly less likely to receive a positive membership or personal training response from both the autonomous and chain fitness centers. Therefore, it is imperative that community sport and fitness coaches, including those from specialized programs (e.g., within Special Olympics), acquire specific training in adapted PA to address unique accommodations, limitations, and engagement techniques (Barak et al, 2019;Pires et al, 2021).…”
Section: Internal Domains-strength and Weaknessesmentioning
confidence: 99%
“…A formação formal, globalmente, é entendida como requerendo diretrizes de admissão, frequência obrigatória, currículos normalizados e culmina com uma certificação (Feu et al,2010;Nelson et al, 2006). No caso do desporto adaptado, este tipo de formação é escasso e dispendioso, o que consequentemente leva a uma aprendizagem por tentativa e erro por parte dos profissionais (Douglas et al, 2017;Pires, Batista et al, 2021). Perante esta prerrogativa Bentzen et al (2020), realizaram uma scoping review com o objetivo de desenvolver o conhecimento específico na área do desporto adaptado, que a satisfação com a vida, pode ser regulada por fatores ambientais e intrapessoais como: idade, género, tipologia da deficiência e tipo de desporto (Moltó & Bruna, 2017).…”
Section: Introductionunclassified